THE PLACE AND ROLE OF TIME IN HUMAN ACTIVITY - Norkulov, D.T. (Journal of Learning on History and Social Sciences, 2024)
Background: Time is a crucial but usually underappreciated aspect of human life and societal development. It has an impact on many aspects of society and serves as both a change indicator and a regulator of human behavior. Specific Background: Despite the fact that societies usually divide time into "working" and "non-working" periods, efficient time management in both areas significantly affects productivity and personal development. Knowledge Gap: While previous research has looked at the social and economic aspects of working hours, less attention has been paid to the overall impacts of time on people's well-being and the development of society at large. The goal of this research is to examine the several ways that time functions in society, with an emphasis on how it affects awareness, work habits, and the advancement of civilization. Findings: The findings show a strong relationship between effective use of working and non-working time and social efficiency, personal motivation, and conformity to the demands of modern society. Numerous elements, such as financial incentives, organizational structure, and individual accountability, further moderate this link. Uniqueness: This research provides a conceptual framework for analyzing "social time," integrating perspectives from the domains of economics, sociopolitics, and culture. Implications: These findings highlight the need for legislation that encourages effective time management, reiterating that good time management can benefit society and increase personal satisfaction.